2017
DOI: 10.21093/ijeltal.v2i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Descriptive Text Writing In SFL Perspectives

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 6 publications
(7 reference statements)
4
22
0
Order By: Relevance
“…Topical themes in the form of the unmarked topical theme were used frequently in all texts. This result supported previous studies conducted by Noprianto (2017) and Potradinata (2018) who also found that unmarked topical theme was the dominant theme in descriptive texts. Regarding the theme progressions, reiteration pattern was a pattern that was used in all texts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Topical themes in the form of the unmarked topical theme were used frequently in all texts. This result supported previous studies conducted by Noprianto (2017) and Potradinata (2018) who also found that unmarked topical theme was the dominant theme in descriptive texts. Regarding the theme progressions, reiteration pattern was a pattern that was used in all texts.…”
Section: Discussionsupporting
confidence: 92%
“…The topical theme is used 60 times and 55 of them are unmarked topical themes. This supports the findings of previous studies conducted by Noprianto (2017); Potradinata (2018) who found that in descriptive texts, unmarked topical themes were the most frequently used theme. Unmarked themes are dominant because for students who are beginners in writing English, the easiest way to compose grammatically correct English sentences is to place pronouns or nominal groups as the subject of the sentence (Halliday in Arunsirot, 2013).…”
Section: The Theme Selection Consistencysupporting
confidence: 91%
“…One of the skills which need to be mastered by the vocational high school students is writing skill, especially a descriptive text. This statement is in line with Noprianto (2017), who stated that descriptive text is one of the text types which is requested to master by secondary schools in Indonesia. However, this type of text is the most difficult for students.…”
Section: Introductionsupporting
confidence: 79%
“…The descriptive text tells about how the characteristics of the subject or the detail description of something. Noprianto (2017) states that as nonfiction genre, descriptive text regarded important to be introduced to the young learners as soon as possible because it is clearly recognized that when students learn nonfiction genres and they actively engage with the world outside themselves.…”
Section: Introductionmentioning
confidence: 99%